The Educator's Portfolio & Curriculum Vitae - Workshop & Resource Guide - Deborah Simpson; Karen Marcdante; Judy Fenzel (Association of American Medical Colleges, 2007)
Abstract Introduction Faculty seeking to advance in their academic careers with an emphasis on education often struggle with how to document their educational contributions in traditional academic curricula vitae (CVs). They may also struggle with expanding an existing CV into an educator's portfolio (EP) where the quantity of an educator's activities (e.g., administrative roles in education, teaching responsibilities, advising/mentoring, awards/recognition as educators, and the products of these activities) may be documented. By developing an EP, faculty members can focus on the evidence of excellence and engagement within the educational community consistent with the precepts of scholarship. Methods This resource contains annotated PowerPoint slides, worksheets for the development of an EP, an instructor's guide, and a resource guide presenting samples of successful educator-focused CVs and associated EPs that demonstrate effective presentation strategies consistent with Glassick's criteria for scholarship. Further, consistent with the findings from the AAMC Consensus Conference on Educational Scholarship, this session highlights key features associated with effective documentation and presentation of educators' contributions for academic promotion. Examples are provided to illustrate how to effectively document the quantity and quality of educational activities as well as how to engage with the community of educators. The resource guide includes a standard academic CV format, an expanded CV format used by educators, seven paired promotion CVs/EPs and additional samples of EPs to highlight selected topics (e.g., grants, community-academic partnerships, etc.). While the CV/EP examples are timeless, updated references are provided in an accompanying instructor's guide. Results With more than 15 years of experience in capturing and documenting educator's excellence, our CV and EP examples have been used in multiple workshops at local, regional, and national levels. Several Medical College of Wisconsin CV and/or EP's were abstracted and included as exemplars at the AAMC-GEA Consensus Conference on Educational Scholarship. Discussion Often academic CVs and association promotion documents are private documents, rarely shared with colleagues beyond high-stakes decisions. This compendium makes what educators do public and available for peer review in a very straight-forward, non-threatening, user-friendly format for others to build upon consistent with the work of Lee Shulman and others at the Carnegie Foundation for the Advancement of Teaching. Preparation of the educator focused CV and EP require that faculty assume primary responsibility for the on-going documentation of their activities that are drawn from and/or contribute to the knowledge base in medical education.